Development and validation of mental toughness questionnaire among volleyball players in Malaysia - Chen, Liew Guo (2020)
Athletes’ performance is often affected by various psychological factors, which should be taken seriously to ensure peak performance during competitions. Mental toughness is one of the psychological attributes commonly discussed by sport psychologists to influence athletic performance. Developing and nurturing these attributes can help athletes to control their thoughts, words, actions, and emotions, which will ultimately lead to optimal athletic achievement. Currently, to the best of our knowledge, no studies have been conducted to examine mental toughness among volleyball players in Malaysia. Understanding an abstract concept, such as mental toughness, requires a sound measurement instrument. Moreover, given the lack of specific measurement instruments in volleyball, it is crucial to develop an appropriate questionnaire to assess mental toughness for this sport. In this study, the present researcher is attempting to converge the available literature in the research of mental toughness to find the most consistent predictors of mental toughness. Based on these predictors, a measurement instrument has been developed and validated. This study hopes to identify the attributes of mental toughness, specifically for the Malaysian volleyball players. The study began with the item construction procedure, which involved five experts in assessing the relevance of the initial items to the proposed subscales. The experts were asked to select 10 most appropriate and relevant questions for each factor. Next, based on these 40 selected items, another five experts in the field of sport psychology, coaching, and elite volleyball national players with approximately fifteen years’ experience were identified to provide expert assessment regarding the content of the initially selected items. The present study employed a cross-sectional study design, validating the developed questionnaire to measure pertinent factors related to mental toughness. It was divided into two phases. Phase 1 was conducted among competitive athletes who represented the state team in Malaysia. This is followed by Phase 2, which was conducted among volleyball players who represented teams from school, university, district, state, and national levels. Using purposive sampling, the participants were informed that their participation was entirely voluntary; those who were interested completed the self-administered questionnaires. The data were analysed using SPSS 25 for descriptive statistics, and Mplus version-8 was used for the confirmatory factor analysis. The mean differences of the mental toughness subscales among the volleyball players’ levels of involvement were analysed using one-way ANOVA. The results found four most consistent factors through the converging process, namely attention control, self-belief, commitment, and desire for success. For Phase 1, a total of 404 state-level athletes participated in the study (males 66.1%, females 33.9%), with a mean age of 16.44 (SD=2.57). In the testing measurement model of the newly developed questionnaire, the final model consisted of 35 items, which resulted in a good fit to the data [CFI = .897, TLI = .891, SRMR = .052, RMSEA (90%CI) = .042 (.038, .046)]. The internal consistency coefficients measured using Cronbach’s alpha were .849 for attention control, .837 for self-belief, .867 for commitment and .849 for the desire to succeed. The ICC value for the test-retest reliability ranged from .620 to .727 among the newly developed questionnaire subscales. For Phase 2, a total of 272 volleyball players from school, university, district, state, and national levels participated in the study (males 56.6%, females 43.4%), with a mean age of 17.33 (SD=3.96). In the testing measurement model of the newly developed questionnaire, the final model consisted of 35 items that resulted in a good fit to the data [CFI = .903, TLI = .901, SRMR = .055, RMSEA (90%CI) = .046 (.041, .052)]. Internal consistency coefficients measured by Cronbach’s alpha were .845 for attention control, .850 for self-belief, .870 for commitment and .849 for the desire to succeed. There was a significant mean difference between the mental toughness levels of volleyball players from school, university, district, state, and national levels in self-confidence and sustained attention. The findings indicated that the newly developed questionnaire could be used to assess the mental toughness levels of volleyball players. This newly developed information is important for the sport psychologists and coaches of our nation so that they could apply it to our national athletes to improve their sporting performance.